The Ecuadorian university and the development of communication skills in English - Andrade Mendoza, José Luis; Vallejo Barreno, Carina Fernanda; Lechón De La Cruz, Marjory Estefanía (Journal of the University of Zulia, 2023)
When it comes to gaining communication skills in English, its importance cannot be disputed. Those who carry out higher education studies need to have the potential to keep up to date, the students to learn and the teachers to teach. Thus, this article aims at a critical-hermeneutic reading of the current circumstances in which the teaching-learning process of the English language takes place in the university context of Ecuador. Part of a documentary design that collects information on pedagogical strategies in teaching English, considering the importance of this language in the process of intellectual and labor pursuit of university students. It is known that, as a result of some curricular changes that occurred in the second decade of the 21st century, the Ecuadorian education system includes the teaching of English in Basic General Education and in Baccalaureate, something that promotes its assessment at higher levels. In the university environment, the analysis of the literature on the subject and the critical hermeneutic reading reveals that the boredom of the students and their lack of motivation, has among other causes, the little innovation of the teachers, who tend to work according to the reading textbooks with few incentives for meaningful and collaborative learning. Meanwhile, it is urgent that teachers introduce new methods and strategies at the level of university education that aim at the development of communication skills to enhance the intellectual and socio-productive progress of students and graduates of Ecuadorian universities.